Getting animated about trauma – Using video animation as part of informed consent. Issue 11 (November 2020) - Reynolds, P.M.; Mostafa, A.; Butler, M.; Middleton, R.G.
Abstract: Introduction: Trauma patients are often required to make an informed decision about surgery within a short space of time. Coming to terms with their injury may mean they have limited bandwidth for absorbing information, and it may be that they don't appreciate the risks and benefits of surgery discussed during consent. Current consent practice puts the emphasis on the clinician to ensure that all reasonable steps have been taken to explain risks and benefits to patients. We propose the use of video animations that patients can watch prior to surgery as a means of improving their understanding and overall experience. Methods: The video script was written and evaluated so that a high standard was achieved using the "Discern" instrument. The experiences of a focus group of 5 patients were used to guide script content. Using GoAnimate (GoAnimate Inc., San Mateo) a video was made with voice over provided by local drama students. The video was shown to 30 consecutive patients over a 2 month period. We included any patient with an ankle fracture managed operatively who had been consented (form 1). Evaluation consisted of interview with patients consisting of 2 focussed questions and one open. Responses to the questions were collated and grouped into positive and negative descriptors. Results: 68 (81%) positive descriptors were recorded from patients' interviews versus 16 (19%) negative. Positive descriptors related to improved retention, information giving, technical detail, consolidations of information given during consent. Negatives were caveats that video couldn't replace face-to-face consent, the degree of detail being off-putting and not adding anything to standard consent. Conclusion: The video was well received by patients with subjective improvements being made to their understanding, retention and sharing of technical detail. The face-to-face discussion between patient and doctor remains very important to them and the video should look to augment this.